Social Networks and the 1912 Commemoration of the “Brock Centenary” - Holdsworth, Peter (Ontario History)

(untitled) (The Ontario Historical Society, 2017)
In 1912, the General Brock Chapter of the Imperial Order Daughters of the Empire (IODE) unveiled a monument to General Sir Isaac Brock in Brockville, Ontario. This monument represented just part of the efforts of a network of mostly Anglo-Saxon women from the IODE, United Empire Loyalists of Ontario, and Ontario Historical Society to celebrate the centenary of the War of 1812 as the “Brock Centenary.” The context of the rise of the “Brock Centenary” is investigated by applying social network theory to historical memory studies, re-interpreting historical evidence from 1898 to 1912. An analysis of membership lists both reaffirms some previous arguments around imperial and feminist ideals and also points to other promising avenues of inquiry regarding the importance and influence of the groups and women involved.